Peningkatan Kemampuan Digital Marketing dan Kreativitas Pembuatan Konten The Taran Villas Lembongan, Nusa Lembongan, Klungkung - Ni Kadek Sioaji Yamawati; I Made Astu Mahayana; Dewa Ayu Dyah Pertiwi Putri; Ni Luh Putu Indiani (Universitas Warmadewa, 2024)
Nusa Lembongan has experienced rapid development in the tourism sector. However, behind the development of the world of technology and tourist accommodation in Nusa Lembongan, partners are still unable to utilize digital marketing as an effort to increase their revenue. The problem faced is the lack of knowledge about the importance of promotion through digital platforms. The second problem is the lack of awareness about the importance of promotional strategies. Third, the lack of skills in using information technology. Fourth, the lack of ideas in creating interesting content. The last problem is the lack of updates on current social media developments. The solution we provide for the first problem is to socialize the importance of digital marketing. The solution to the second problem is to conduct socialization and content creation assistance. For the third problem, assistance in the use of information technology in the form of application-based digital marketing models and websites as portfolios. The solution to the fourth problem is to provide assistance in creating content as well as providing training in creating content that can become advertisements that attract consumers. For the last problem, provide training on advertising language in attracting the right target market. The success of the activity is measured using indicators: achievement of training objectives, achievement of planned targets, and program sustainability. The level of achievement of these three indicators shows an average value above 75 percent so that this community service activity has gone well. The programs in this community service activity need to be maintained by improving the quality of active promotion on the internet and social media, focusing on the target market, maintaining product content engagement on Instagram social media, redeveloping caption ideas with good advertising language, adding skills to create attractive visual and audiovisual content on other social media.